From All‐Printed 2D Patterns to Free‐Standing 3D Structures: Controlled Buckling and Selective Bonding. Issue 5 (26th March 2018) - Yin, Lu; Kumar, Rajan; Karajic, Aleksandar; Xie, Lingye; You, Jung‐min; Joshuia, Davina; Lopez, Cristian Silva; Miller, Jennifer; Wang, Joseph
Abstract: Current methods to create 3D structures are limited to few materials and designs, are costly, and have low processing throughput. Planar designs (of printed sacrificial, flexible, and guiding layers) fabricated by thick film technique that can reversibly fold between their 2D and 3D forms through compressive buckling and selective bonding is reported in this work. Versatile ink compositions based on a wide variety of materials (e.g., carbonaceous, polymers, and nanomaterials) are used along with screen printing technique for creating variety of desired 3D structures, such as spirals, squares, and spikes. Various composite inks are printed onto substrates containing a printed sacrificial layer for selective binding, and the substrate can be prestretched for a controlled buckling process. Removal of the sacrificial layer and release of the strained substrate leads to the folding of the flat printed structures into targeted respective 3D architectures. Such use of planar screen‐printed layers to create 3D shapes brings several technological advantages, including broad selection of materials, large‐scale processing at low cost, and incorporation of numerous functional technologies. The successful control of such printed 3D architectures offers a promising route to enable numerous applications based on large variety of materials. Abstract : An all‐printed 3D planar design can be fabricated using 2D planar designs with compressive buckling and selective bonding. Wide variety of materials are used along with screen‐printing technique for creating variety of desired 3D structures, such as spirals, squares, and spikes. 3D structures fabricated in this method shows superior mechanical and electrical performance during large deformation.